The role of ECB communication in guiding markets - Marc Anderes; Alexander Rathke; Sina Streicher; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2019)
Economists and central bankers nowadays believe that forward guidance has become more important in a world in which key interest rates have hit their effective lower bounds (ELB). In case of the European Central Bank (ECB), this should have increased the informational content of the introductory statements at the press conference following ECB policy meetings. We examine whether this form of ECB communication adds information to a shadow interest rate that summarises the overall policy stance as interpreted by financial markets. To measure communication, we use information based on ECB press releases distinguishing between topics like inflation, the real economy and monetary developments. We also look at the effect of communication on consensus expectations about key macroeconomic variables. Especially ECB's assessment of the economy, i.e. communication related to economic growth, triggers movement in financial markets and thereby the shadow rate. Communication of the ECB through its press releases also causes professional forecasters to change their outlook. Not only their growth forecasts are affected, also their expectations for M3 growth and inflation are.
Keywords: E3; E43; E51; E52; E58; 330; Central bank communication; shadow rates; consensus expectations; ECB; euroarea; money growth